investasi emas melalui produk pembiayaan BSi cicil emas untuk jangka panjang - ahmad febrianto; fikri ahmad ghani (Nurul Jadid University, 2023)
Investment is one way to get profit or income. Gold investment is one of the investment alternatives for individuals, companies or institutions that have financial freedom to invest. The purpose of this study is to find out what are the advantages of investing in gold through gold installment financing products for the long term. This research method uses qualitative methods using descriptive types in the form of observations, interviews and documentation conducted by researchers. The result of this study is the investment benefits contained in this product, namely the benefits obtained from investing in gold, liquid (can be cashed out by mortgage for urgent needs), profitable (cheap tariffs), rising gold prices that continue to increase every year, low risk levels, safe (your gold is insured) those are some of the advantages that are the reason for me